Morphometric Analysis of the Facial Profile: Contour of the Side Face and its Variations. Issue 7 (October 2018) - Li, Haijun; Wu, Xianzhu; Zhang, Yidan; Chen, Feng
Abstract : Abstract: Much research has been conducted on the morphological characteristics of the Chinese. However, very few facial measurements have been documented, especially of the side face. This study uses geometirc morphometric method to analyze the contour and variations of the side face in Bai and Yi ethnic minorities from Yunnan province, China. The mark collection proves that for the Bai ethnicity, the variations of the nose are comparatively large, while the forehead variations are small. Variations around the lips and the chin are the largest. For the Yi ethnicity, the forehead also witnesses small variations and the nose again has large variations. The area around the glabella has large variations. Through the comparisons, the area around the glabella tends to extrude more in males both in Bai and Yi. The situation, however, is much more different when it comes to the trichion landmark collection where we see an apparent intrusion in males. For the trichion, Yi people are more intruded than the Bai. Similarities between Bai and Yi are demonstrated by principal component analysis: one can roughly set the males apart from the females using the vertical axis. Profile at the end of horizontal axis suggests that the female facial profile has the following features: the nose is not so prominent as the male, the forehead and the nose are linked by an noticeable arc, the forehead is comparatively steep and is almost in a vertical plane with the lips and the chin. By comparison, the male has a flatter forehead, a more prominent nose, an obvious sellion, and an intruded chin. The common morphologic features of the Chinese face may be reflected through these similarities.